STRATEGI DAKWAH POPULER HANAN ATTAKI TENTANG CINTA DAN ISLAMISME - Ahmad Taufiqur Rohman (Al-Mishbah: Jurnal Ilmu Dakwah dan Komunikasi, 2019)
This paper examines the new Islamic promoter Hanan Attaki who can spread his Islamism through various media, especially in his Youtube account. This paper aims to describe the spread of popular Islamism as a defense to self fortify from western popular culture, and this distribution is greatly facilitated by democracy. This article becomes essential because it shows the spread of Islamism in Indonesia that characterized by motivation and self-development, so that be able to entertain and embrace the youth. The spread of Islamism shows that religion does not want to be placed in private space, but also public space. At the end of this session, it was concluded that the spread of popular Islamism among young people aims to form the justification of the ideal type of Muslim youth today.